Тенденции изменений в оценке жизненной ситуации учасниками ликвидации последствий аварии на Чернобыльской АЭС - Кузьменко, Т. (Социология: теория, методы, маркетинг, 1999)
In the article based on sociological research data, the author has discussed how those who took part in doing away with Chernobyl pollution (the liquidators) estimate their living conditions and how it depends on deterioration of their physical and mental health. As the result of this deterioration, the liquidators are less successful in labor market and in providing their families, their family problems have been deteriorated too. 48,9% of the liquidators regard themselves to be victims. It is more than the same indicator among their surrounding. As to the author, this indicator plays the most important role in forming the outlook and passive life position of the liquidators.